Pemanfaatan Liveworksheets dalam Pengembangan E-LKPD Numerasi Berbasis Ke-Islaman untuk Melatih Kemampuan Berpikir Tingkat Tinggi - Yanti, Aning Wida; Sutini; Putri, Alfina Rifky Taftiana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to develop E-LKPD based on Numeracy Literacy Integrated with Islamic content with the help of liveworksheets to train students' critical thinking skills. The type of research is development research. The development procedure uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The product developed is E-LKPD—number and Algebra Material. Based on the research results, it was found that (1) The E-LKPD development procedure uses the ADDIE Development Model, whereas, in the Analysis Stage, data was obtained that the use of learning media was still less than optimal, especially for materials considered difficult by students. In the Design Stage, an E-LKPD design was produced. In the development stage, E-LKPD was developed, validated, and revised based on input from the validator. In the implementation stage, the process of implementing E-LKPD for students was carried out. In the Evaluation Stage, an assessment of the effectiveness of E-LKPD was carried out; (2) The E-LKPD developed meets the criteria of